2015
DOI: 10.1186/s13049-015-0125-z
|View full text |Cite
|
Sign up to set email alerts
|

Survival predictor for penetrating cardiac injury; a 10-year consecutive cohort from a scandinavian trauma center

Abstract: BackgroundPenetrating cardiac injuries in Europe have been poorly studied. We present a 10-year outcome for patients with penetrating heart injuries at Oslo University Hospital.MethodsData from 01.01.2001 until 31.12.2010 was collected from the Oslo University Hospital Trauma Registry and from the patients’ records.ResultsThirty-one patients were admitted with a penetrating cardiac injury. Fourteen patients survived (45 %). Four out of 8 patients (50 %) with gunshot wounds survived compared to 10 out of 23 (44… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
47
0
10

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 20 publications
5
47
0
10
Order By: Relevance
“…We observed that most frequently injured cardiac chamber was right ventricle followed by right atrium and left ventricle respectively. These findings are in accordance with the published literature 25, 26…”
Section: Discussionsupporting
confidence: 94%
“…We observed that most frequently injured cardiac chamber was right ventricle followed by right atrium and left ventricle respectively. These findings are in accordance with the published literature 25, 26…”
Section: Discussionsupporting
confidence: 94%
“…The overall mortality rate of patients who underwent surgery because of penetrating and blunt cardiac injury was 40.54%. On comparing with other studies, the overall mortality rate was 55% in a study conducted by Kaljusto et al and was 27.3% in a study conducted by Aksoyek et al (12,13) . Vital signs on admission can change from cardiac arrest to a completely stable status (14) .…”
Section: Discussionmentioning
confidence: 92%
“…It also enables in achieving access to all regions of the heart, including the right heart and both the pleuras (3,21) . Kaplan et al used median sternotomy as an initial incision in 28.57% of patients and Kaljusto et al used it in 35% of patients (10,13) . Aksoyek et al have preferred median sternotomy in all patients except one patient (12) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5/2017 omtales økende antibiotikaresistens (1) og bruk av bredspektret antibiotika ved urinveisinfeksjoner på sykehjem (2) med budskap om å følge de nasjonale retningslinjene for antibiotika bruk i primaerhelsetjenesten (3). Vi har nylig publisert en evaluering av urindyrkningssvar og empirisk behandling hos 161 ikke-gravide kvinner med mistenkt akutt cystitt i en solopraksis (4). Vi fant signifikant oppvekst hos 62 % av 126 pasienter som startet antibiotikabehandling.…”
unclassified